2011
DOI: 10.1002/bbb.326
|View full text |Cite
|
Sign up to set email alerts
|

Impact of distributed storage and pre‐processing on Miscanthus production and provision systems

Abstract: Distributed storage and pre-processing of biomass feedstock at satellite storage locations (storage depots) has been proposed in literature to reduce costs and improve effi ciency of the supply system. The performance of such a system, however, has not yet been rigorously quantifi ed and compared with conventional alternatives. This work presents such an analysis using the BioFeed optimization model. BioFeed is a system-level model that optimizes the important feedstock production activities and determines the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The study concluded that the commodity system's GHG emissions are about 4% lower, while consuming approximately the same total energy as the conventional system. The study also emphasized that the processing technology was critical to cost-reduction for the commodity system, a point also addressed by Shastri et al [16] and Uria-Martinez et al [17]. Recently, Argo et al [18] evaluated several environmental sustainability impacts (100-year global warming potential (GWP), rainfall (green water) and groundwater through irrigation (blue water) footprints), and costs for advanced logistics designs that employ densification steps for preprocessing agricultural residues and grasses in depots for long-haul transport to centralized biorefineries designed on the biochemical platform.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The study concluded that the commodity system's GHG emissions are about 4% lower, while consuming approximately the same total energy as the conventional system. The study also emphasized that the processing technology was critical to cost-reduction for the commodity system, a point also addressed by Shastri et al [16] and Uria-Martinez et al [17]. Recently, Argo et al [18] evaluated several environmental sustainability impacts (100-year global warming potential (GWP), rainfall (green water) and groundwater through irrigation (blue water) footprints), and costs for advanced logistics designs that employ densification steps for preprocessing agricultural residues and grasses in depots for long-haul transport to centralized biorefineries designed on the biochemical platform.…”
Section: Introductionmentioning
confidence: 77%
“…If the benefits of handling and storing pellets are quantified, the transportation cost savings can be increased and thus can balance or exceed the cost of densification. However, the total cost of the commodity supply chain system could be higher than the conventional system due to the addition of preprocessing operations and equipment [16,27]. Our objective is to evaluate the spatial variability of life cycle environmental impacts owing to characteristics along the biomass feedstock supply chain (i.e., from field to depot to biorefinery with intermediate transportation and preprocessing steps) that incur variability as a result of the quantity of biomass harvested, collected, stored, moved, and preprocessed prior to long-distance transport to a centralized biorefinery.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-commodity flow mathematical model Impact of distributed storage and pre-processing on Miscanthus production and provision systems Shastri et al [15] Analyze the cost reduction from implementing distributed storage and pre-processing at satellite storage locations. Feedstock: Miscanthus.…”
Section: Discrete Event Simulation √mentioning
confidence: 99%
“…The scope of the formulation covers from the feedstock suppliers to the biofuel customers. Shastri et al [15] formulate a MILP model (e.g., BioFeed) to maximize the profit of the system (i.e., Miscanthus production and provision system). Other papers such as Larasati et al [17] explain the dynamics between competing performance measures, such as the trade-off between switchgrass transportation cost and the economic scale of cellulosic ethanol production.…”
Section: Discrete Event Simulation √mentioning
confidence: 99%
See 1 more Smart Citation